(untitled) (Global Journal of Human-Social Science, 2024)
Background Gaining a comprehensive understanding of the teacher socialization process is essential to promote the physical education profession as it contributes to the improvements of recruitment retention preparation and support for physical education teachers There is a gap in teacher socialization research that spans the lives and careers of physical education teachers Purpose Using a critical incident technique CIT the purpose of this study was to gain a holistic understanding of the teacher socialization process in physical education guided by the occupational socialization theory OST framework Method Participants in this study were two physical education teachers located in one state in the Western United States representing mid- and late-career physical education teachers A comparative case study design was employed to investigate the socialization of physical education teachers using critical incident timelines semi-structured interviews and follow-up interviews The timelines and interview transcripts were analyzed using thematic analysis and cross-case comparison Trustworthiness was established using several techniques including triangulation peer debriefing member checking and an audit trail Findings The two cases of Jayden and Tara explored the socialization of two physical education teachers over their lifespan showcasing the key factors both positive and negative that influenced their development Results are represented according to the three phases of OST e g acculturation professional socialization and organizational socialization phases for Jayden and Tara respectively Jayden s acculturation was influenced by sports and a coaching background harmful behaviors of friends parent expectations and inspirational coaches His professional socialization was shaped by physical education teacher education PETE coursework and influential agents Organizational socialization for Jaylen was influenced by students needs supportive agents classroom teachers perceptions of his subject and a value of physical education Additionally Tara s acculturation was influenced by a relationship with a physical education teacher being disinclined towards academic engagement in practical courses and a passion for working with children Her professional socialization was shaped by evolution of the PETE programme impact of PETE faculty having a quality cooperating teacher and a former physical education teacher Organizational socialization for Tara was impacted by previous physical education experiences continuing connection with the PETE programme influential agents as well as marginalization and burnout